O-215 Embryo developmental competence of de novo male gametes in a novel three-dimensional culture. (30th June 2022) - McKnight, M; Xie, P; Rosenwaks, Z; Palermo, G.D
Abstract: Study question: Are de novo gametes generated from mouse embryonic stem cells (mESCs) in a novel three-dimensional (3D) culture system capable of supporting full preimplantation development? Summary answer: A novel 3D culture system yielded de novo male gametes capable of fertilizing an oocyte and supporting full preimplantation development. What is known already: In regenerative medicine, several 3D culture systems have been shown to be capable of producing functional tissue implants. In reproductive biology, recent studies have reported preliminary success in generating functional de novo gametes through soft-agar culture and testicular organoids, in the mouse model. However, a heterologous transplantation technique is required to obtain functional gametes. Study design, size, duration: mESCs were first cultured on a gelatin-coated 6-well plate with fibroblasts in monolayer and later spherified using sodium alginate. Spheres were submerged in specifically designed conditioned media to encourage differentiation of the mESCs into germ-like cells. Over the course of differentiation, cells were assessed for germ cell differentiation biomarkers. Considering that normal spermatogenesis occurs in 30 days, utilization of the de novo gametes was planned for days 15, 22, 29, and 36. Participants/materials, setting, methods: mESCs were differentiated by submerging the spheres in EpiLC medium containing Activin A, bFGF, and KSR for 3 days followed by PGCLC medium containing BMP4, LIF, SCF, and EGF for up to 36 days. Differentiation was assessed for markers DAZL (spermatogonium), VASA (spermatocyte), BOULE (post-meiotic stage), and acrosin (spermatid). Differentiated cells were then injected into oocytes and activated by calcium ionophore. Embryo development was monitored in a time-lapse incubator. Main results and the role of chance: Expression of DAZL in 20% and VASA in 15% of the cells at day 3 demonstrated progression into spermatogenesis. On day 10, DAZL and VASA were assessed again, revealing increases to 45% and 18%. A small proportion of cells expressed post-meiotic biomarkers, BOULE (1%) and acrosin (2%). On day 15, VASA expression plateaued at 17%, BOULE expression peaked at 10%, and acrosin reached 5%. On day 22, expression of VASA increased slightly to 19%, BOULE decreased to 8%, and acrosin peaked at 7%. On day 29, VASA expression peaked at 20%, acrosin expression remained stable at 7%, and BOULE expression dropped to 2%. On day 36, VASA was still expressed at 13%, and few cells expressed acrosin (1%); there was complete loss of BOULE expression. Our mouse ICSI control achieved 89.2% fertilization and 77.8% blastocyst rates. De novo gametes were injected into oocytes on days 15, 22, 29, and 36, achieving fertilization rates of 35.0%, 61.1%, 81.8%, and 75.0%, respectively. Correspondently, hatching blastocysts were obtained at rates of 5.0%, 16.7%, 36.4%, and 8.3%, respectively. Limitations, reasons for caution: Despite the ability to fertilize normally, the blastulation rate remained suboptimal. Most importantly, the ability to generate live offspring still needs to be documented. Wider implications of the findings: Our novel 3D differentiation model can generate functional gametes and is aimed at obviating the need for allo-/xeno-geneic transplantation. If reproducibility and the ability to obtain healthy offspring are confirmed, this method may represent a tool for achieving neogametogensis in mammals. Trial registration number: N/A